Draft precis of evidence to be given before the Departmental Committee on Midwives
1928-09 1928 1920s 6 pages 4. in the use of instruments of such a nature - though the latter, we understand, is really of a specialist nature. The multiplying of reports and their growing complexity is perhaps inevitable and in order to do these satisfactorily for the use of the doctor as well as the public authorities the midwife needs a careful and widely educative training in her work. 12. We should not be content with less than two years' training, though we think entrants for such training will be difficult to get until the conditions of work of the midwife are improved. In the case of a trained nurse one year's special training as a midwife should be sufficient. 13. The training whatever its period should be divided between a general theoretical training and practical work. 14. The training should be in co-operation with the medical schools and the theoretical side should be conducted by highly qualified teachers and the practical training carried out under close supervision by medical practitioners with a special qualification. Such training might be in connection with Maternity Homes which are under the Local Authority and have on their staff highly qualified consultants who would supervise the training given. 15. The training should be carried out according to the rules and curricula approved by the Central Midwives' Board. 16. It is clear that there is now not sufficient provision for training and until such provision is ample and the number of midwives sufficient the first opportunities should be given for practical work to all those who are going to practice. In order to be sure of getting the right entrants to the profession Local Authorities should have the same power to pay for training as they have for the training of teachers. Bursaries and scholarships should be available for suitable entrants. 17. We should prefer the service to be organised by the Local Authorities. We recognise that there is a difficulty inasmuch as the District Nursing Association have already done much work in this respect, and we think this may best be met by the Local Authorities gradually assuming a greater share in the work of the Association and greater control, until finally it becomes a public service under the Health Authority. Wherever the service is now insufficient, however, the Local Authority should appoint midwives under its control. Its relation to Health Insurance could be dealt with by payments from Approved Societies to the Local Authorities. 18. We note that Municipal Midwives already appointed get very varying rates of salary. In our opinion the salaries should be approximate to those of trained and certificated teachers and should have coupled with them superannuation allowances at 55 or at any previous time when the condition of health necessitated retirement. 19. Working in the way we have proposed with a doctor, the midwife ought to be able to undertake with reasonable care 120-150 cases a year. 292/824/1/116